Rancangan Kawasan Kota Tua Teluk Betung Selatan Sebagai Destinasi Wisata Kota Bandar Lampung - Andyzon Octadinata; Citra Persada; Endro Prasetyo (LOSARI Jurnal Arsitektur, Kota dan Permukiman, 2020)
The Design Area Of South Teluk Betung Old Town As Tourism Destination In Bandar Lampung City Bandar Lampung City has an old town area which is located in the South Teluk Betung District. This town has existed since 1839, and the area is a center of trade and services which became the forerunner to the formation of the Capital of Bandar Lampung before being moved to Tanjung Karang. The South Teluk Betung Old Town area has heritage buildings with some variety of architectural styles such as: Thay Hin Bio Temple with Chinese architecture style, Jami "Al-Anwar Mosque with Islamic architecture style, and several houses and shophouses has been built with Indische architecture and Colonial architecture. The research method used is “Appreciative Inqury (AI)” by looking at the potentials that exist in the region. The design concept used is “heritage tourism” which is the concept of urban tourism that utilizes heritage as a tourist attraction. The design approachment is utilizing to build the environment of a city that has its own historical value. Tourists will be invited to appreciating and interpreting the heritage objects that has been observed. The results of this research is urban design elements The South Teluk Betung Old Town such as: pathways, nodes, landmarks, signage, the concept of Green Open Space, waste management, fire disaster mitigation, tsunami disaster mitigation and the concept of heritage tourism.